ANALISIS PENGARUH PENGGUNAAN METODE GASING TERHADAP PEMAHAMAN MATEMATIS SISWA DI SEKOLAH DASAR - Matahelumual, Michelle Miranda Elizabeth; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A solid understanding of mathematical concepts at the elementary school level is crucial as a foundation for mastering more complex material at higher levels of education. However, current classroom conditions reveal that many students struggle to grasp basic mathematical concepts due to a lack of varied and contextual learning methods. This study aims to analyze the impact of the GASING method (Gampang, Asyik, dan Menyenangkan — Easy, Fun, and Enjoyable) on elementary students' mathematical understanding using a qualitative approach through a literature review. Data were obtained from an analysis of ten relevant research journals published within the last seven years. The findings indicate that the GASING method consistently enhances students' mathematical comprehension, both cognitively and affectively. Learning becomes more enjoyable, students are more engaged, and academic outcomes show significant improvement. These findings suggest that the GASING method can serve as an innovative and effective alternative for improving the quality of mathematics education at the elementary level. Recommendations include the broader implementation of the GASING method and further research in inclusive classroom settings and the development of higher-order thinking skills.